A Study of the Propagation and Cultivation of Gethyllis multifolia and G. villosa. - Daniëls, Christiaan Winston (Cape Peninsula University of Technology, 2007)
Gethyllis multifo/ia and Gethyl/is villose (Family: AMARYLLIDACEAE) are indigenous geophytes, growing naturally in the Worcester area, Western Cape. G. muliiiolie falls in the Vulnerable category of the Red Data List of Southern African Plants while G. vil/osa is not threatened at all. Both these species are winter growers and start their growing phase between March and April. These bulbs start their dormant phase between September and October when their leaves start to die down. Flowers of both species are short-lived and borne towards the end of November and early December when no leaves are present. The leaves and berries are simultaneously pushed above ground at the onset of the new growing phase. The fruit of some Gethyl/is species is sweet, juicy, pleasantly aromatic and good to eat and has medicinal properties for the cure of various ailments. The genus is difficult to propagate asexually and very little is known about its propagation and cultivation. The fragrance and medicinal value of the fruit of G. multifolia necessitates future research in the commercial production of this species. A habitat observation study of the two species was conducted to assess the vulnerable status of G. multitolie. Asexual propagation experiments were conducted to find ways of reproducing these two species successfully. A hydro culture study was also conducted to ascertain whether this method of cultivation could be incorporated in the general cultivation of the two species. Finally an in vitro propagation study was conducted to look at faster methods of reproducing these two species. This is of extreme importance in the conservation of the vulnerable G. multitolie. Leaf, root and basal plate cuttings were unsuccessful with no rooting in both species. G. mulfifo/ia bulbs were propagated successfully using twin scaling, bulb cuttings, scooping and scoring propagation techniques with between 80% and 100% rooting success. G. vil/osa was unsuccessful using the above propagation techniques with a 0 - 40% rooting rate. Although Gefhyl/is species in general are sensitive to over-watering, the hydro culture experiment with the sub-irrigation system and leca pellet medium proved to be an effective method of cultivating both species throughout the growing phase. G. mulfifo/ia proved to be unsuccessful during the initial in vitro propagation experiments with no surviving explants during the initiation phase. Results improved with an increased number of trials. It is possible to grow both species by means of in vitro propagation, but more emphasis in future research, should be placed on the multiplication aspect of G. mu/tifo/ia, since not many new buibiets were produced. It was observed through this study that grazing domestic livestock, urban expansion (this includes agricultural extension) and in some cases the lack of interest shown in our indigenous plant species, are some of the main factors influencing the decline in numbers of this species. It is also recommended that more emphasis be placed on the conservation of South Africa's indigenous flora and that the vulnerable status of G. multifolia according to The Red Data List of Southern African Plants, be changed to the "Endangered category" as the factors causing its decline continue to increase.
Thesis (MTech (Horticulture))--Cape Peninsula University of Technology, 2007.
Keywords: Plant propagation --South Africa -- Western Cape; Horticulture